PERBANDINGAN HASIL BELAJAR SISWA KELAS VI SD NEGERI SARIREJO 03 DENGAN SISWA KELAS VI SD NEGERI SUKOHARJO 03 TAHUN PELAJARAN 2018/2019 - Rosa Novita Pitaloka; A.Y. Soegeng Ysh; Asep Ardiyanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Learning achievement is the relationship between several factors that can influence both in oneself (internal factors) and from outside (external factors). The learning achievements of students in the city as well as in the village should be the same. Because all have the same right to education and facilities. The difference in the learning outcomes of grade VI students of SDN Sarirejo 03 with SDN Sukoharjo 03 is the formulation of the problem to be studied. The purpose of this study is to find out whether there is a comparison of the learning outcomes of students of SD Negeri Sarirejo 03 with SD Negeri Sukoharjo 03 using national examination scores in the 2018/2019 Academic Year. The type of research used is quantitative with Comparative Techniques and using T-Tests. The method of data collection is carried out by means of interviews, observations and documentation. The collected Writing data was analyzed using the t-test formula. Based on the results of data analysis, it was found that there were differences in the value of SD Negeri Sarirejo 03 with SD Negeri Sukoharjo 03. Thus the tt (t of the table) for a significance level of 5% is 2.042, while the t0 (t of observation) is 2.520. Then the to (t of observation) is greater than the tt (t of the table). If written in the form of numbers, it is 2,520>2,042. The results of the writing can be concluded that there are significant differences in the learning outcomes of SD Negeri Sarirejo 03 with SD Negeri Sukoharjo 03.